PENGARUH PERSEPSI KEADILAN ORGANISASIONAL DAN PEMBERDAYAAN TERHADAP KEPUASAN KERJA KARYAWAN BANK SYARIAH MANDIRI PEKANBARU - Putri, Suchi Novia; Rifqi, Ahmad; ', Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine the effect of Perception Organizational Justice and Empowerment on Employee Satisfaction of Bank Syariah Mandiri Pekanbaru. The population in this study were all employees of Bank Syariah Mandiri Sudirman branch. Total number of employees is 58 people. Given the limited number of population, the authors conducted a census sampling technique, ie to the entire population of 58 people. Analysis of data using multiple linear regression with SPSS program. Based on the results of data analysis known that organizational justice and empowerment simultaneously affect the job satisfaction of employees of Bank Syariah Mandiri Pekanbaru. Justice organizational partially influence on employee job satisfaction Bank Syariah Mandiri Pekanbaru. Empowerment partially influence on employee job satisfaction Bank Syariah Mandiri Pekanbaru. It is expected to head of the company in order to educate employees so easy to get along with fellow employees in the company (improve cooperation). For example by suggesting employees to greet each other in the company so that a sense of community arises in the employees so that they are easy to get along with each other employees who have been working and the employees who have performed above average or very maximum.Keyword : Justice organization, Empowerment, and Satisfaction.